PENGUJIAN TOKSISITAS EKSTRAK DAUN WEDUSAN (Ageratum conyzoides) TERHADAP ULAT JANTUNG KUBIS (Crocidolomia binotalis Zeller.) - Subagiya Subagiya; MK Himawati; Puspita Wulandari (Universitas Sebelas Maret, 2009)
The research concerning about the toxicity of Wedusan extract leaves on Cabbage-heart caterpillar (Crocidolomia binotalis Zeller) has been conducted in the Laboratory of Plant Protection and Green House of Agriculture Faculty, Sebelas Maret University Surakarta. The experiment was initiated in January 2006 until January 2007.The experimental design was a randomized complete with four replications. Toxicity of Wedusan leaves extract was tested at two stages. The first stage test consisted by six level concentrations, there were 0, 50, 100, 200, 400 and 800 g dried wedusan extract leaves (DWEL)/l distillated water. The second test was primarily experiment consisted by seven level concentration, were 0; 31,25; 62,5; 125; 250; 500 and 1000 g dried wedusan extract leaves (DWEL)/l distillated water. Those experiments used by Leaf Deep Bioassay method. The treatment on green mustard by spraying method was to know effectiveness of Wedusan leaves extract as botanical pesticide if it would be applied on crop. The concentrations were used in this experiment was 0, 67.5, 300, 600, and 900 g DWEL/l distillated water.The result of this experiment showed that the wedusan leaves extract was toxic for C. binotalis larvae. Explanation of Wedusan leaves extract at 250 g/l able to reduce 44.83% of pupation. 56% of adult emergences, 45.3 egg production, 72.66 hatched larvae, and 42.3 eggs hatched. Wedusan leaves extract sprayed at level concentration 900 g/l effective to reduce the adult emergence.